Spinohypothalamic tract neurons in the cervical enlargement of rats: descending axons in the ipsilateral brain - Zhang, X (J Neurosci, 1995)
Spinohypothalamic tract (SHT) cells are spinal cord neurons with axons that project directly to or through the contralateral hypothalamus. Frequently, SHT axons decussate in the posterior optic chiasm, turn posteriorly and descend to unknown locations in the ipsilateral brain. We attempted to determine the course and the termination of these descending axons. Sixty neurons in the cervical enlargement of rats were antidromically activated initially from the contralateral hypothalamus and then from multiple anterior-posterior levels in the ipsilateral brain. Fifty-three (88%) were backfired with low currents at increased latencies from the ipsilateral brain. The axons of 35 neurons were surrounded with electrode penetrations from which high currents could not activate the neuron antidromically, suggesting the examined axons terminated in the surrounded areas. Seven SHT axons that were surrounded (20%) appeared to terminate in the contralateral hypothalamus, 5 (14%) in the ipsilateral hypothalamus, and 9 (26%) in the ipsilateral thalamus. Fourteen SHT axons (40%) ended in the ipsilateral midbrain mainly in the superior colliculus, cuneiform nucleus or nucleus brachium inferior colliculus. An additional 11 axons were followed even further posteriorly into the ventral pons or rostral medulla. Each of the 26 neurons that could be physiologically classified responded either preferentially or specifically to noxious mechanical stimuli. These results indicate that SHT axons course through a surprisingly long and complex path. After decussating in the hypothalamus, the axons of many SHT neurons descend into the ipsilateral posterior thalamus, midbrain, pons, or even rostral medulla. These axons may provide nociceptive information to a variety of nuclei throughout the diencephalon and brainstem bilaterally.